Uncovering somatic mosaic variants of PIK3CA-related overgrowth disorders – three cases with different clinical presentations - Tooming, M.; Mertsina, P.; Kahre, T.; Teek, R.; Vainumäe, I.; Lilles, S.; Wojcik, M. H.; Ilves, P.; Õunap, K. (Frontiers in Genetics, 2025)
IntroductionPIK3CA related disorders (PRD, OMIM: *171834) are genetic disorders resulting from pathogenic somatic mosaic variants in the PIK3CA gene, which encodes a protein crucial for regulating cell growth and division. PRD typically manifest during the post-zygotic phase, leading to a broad spectrum of overgrowth and vascular malformations affecting various body regions.MethodsConventional diagnostic methods struggle to detect and confirm pathogenic PIK3CA gene variants due to the mosaic nature of these disorders and the limited accessibility of affected tissues. In this study, we conducted comprehensive genomic profiling on a cohort of individuals with PRD to address these diagnostic challenges.ResultsOur analysis revealed significant diagnostic challenges posed by somatic mosaicism in PRD. The comprehensive genomic profiling allowed for the meticulous evaluation of potentially pathogenic gene variants in affected individuals and their corresponding tissues.DiscussionOur findings advocate for the adoption of comprehensive genomic profiling in clinical practice to improve the detection and management of PRD. This approach can enhance patient care by providing a more accurate diagnosis and better understanding of the genetic underpinnings of PRD.